ADVERSITY QUOTIENT TRAINING TO INCREASE THE MOTIVASION AMONG PT. PJB WORKER - Maulida Dwi Pamungkas Hadsal; Mardha Ramadanu (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Adversity quotient training is conducted to increase the motivation of PT. PJB. Adversity quotient can describe motivation, creativity, performance, empowerment, productivity, knowledge, energy, hope and individual happiness in achieving success. This research is an experimental one group pretest posttest study. The subjects in this study were workers at the head office of PT. Java-Bali Power Plant with a work period of 1-5 years. To measure motivation before and after the training uses a scale of achievement motivation. From the Wilcoxon test results obtained Asymp values. Sig (2-tailed) is 0.028 and this value is smaller than the significance value of 0.05 (Asymp. Sig <0.05). This shows that there is a significant difference between the results of the pretest and posttest, meaning that the Adversity quotient training is effective in increasing the achievement motivation of PT. Pembangkit Jawa Bali.